Conceptualising, designing and drafting a monthly multi‐family therapy programme and manual for adolescents with anorexia nervosa. Issue 1 (26th May 2022) - Minier, Lisa; Carrot, Benjamin; Cook‐Darzens, Solange; Criquillion‐Doublet, Sophie; Boyer, France; Barton‐Clegg, Vesper; Simic, Mima; Voulgari, Stamatoula; Godart, Nathalie; Duclos, Jeanne; ,
Abstract: The written transmission of therapists' expertise in manuals is an important issue which is highlighted in the literature. Manuals are essential for research, training and therapeutic guidance. However, the conceptualisation, design and drafting of therapy manuals have received little attention. Our team conceptualised and designed a 10‐monthly session multi‐family therapy programme for adolescents suffering from anorexia nervosa. This paper presents the methodology used to evolve from training and theoretical models to designing a programme and drafting the accompanying manual. We then describe how our team reached a consensus regarding the role to be attributed to food‐related symptoms in the programme. These arduous tasks were rewarded by fruitful discussions among team members, which led to a shared theory of treatment. The methodology presented here is drawn from both the experience of specialised teams and from that of families in providing care to adolescents with anorexia nervosa.